2022
DOI: 10.1136/bmjopen-2022-062192
|View full text |Cite
|
Sign up to set email alerts
|

Severe bronchopulmonary dysplasia in extremely premature infants: a scoping review protocol for identifying risk factors

Abstract: IntroductionThe remarkable improvement in the long-term prognosis of extremely premature infants has led to an increase in the number of cases of bronchopulmonary dysplasia (BPD). BPD affects pulmonary function and developmental outcomes, resulting in high chronic health burdens for infants and their families over the years. Therefore, identifying its risk factors in the early period of life and exploring better prophylactics and treatment strategies are important.The objectives of our scoping review are to sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Levando-se em consideração que a DBP não afeta apenas a função pulmonar e que pode prejudicar o desenvolvimento do indivíduo, identificar os fatores de risco para DBP nos recém-nascidos prematuros e tentar adequar as melhores medidas profiláticas e estratégias para um tratamento direcionado, pode evitar o surgimento de sequelas graves que vão impactar negativamente na vida do indivíduo (Kato et al, 2022) Apesar de inúmeras intervenções serem preconizadas, prevenir a DBP ainda é um desafio. Conforme exposto anteriomente, vários fatores estão envolvidos na patogênese da displasia broncopulmonar em recém-nascidos prematuros, incluindo as variações genéticas e o resultado delas que promove diferenças entre os indivíduos, podendo predispor ou não à DBP.…”
Section: Intervenções Para Prevenir Dbpunclassified
“…Levando-se em consideração que a DBP não afeta apenas a função pulmonar e que pode prejudicar o desenvolvimento do indivíduo, identificar os fatores de risco para DBP nos recém-nascidos prematuros e tentar adequar as melhores medidas profiláticas e estratégias para um tratamento direcionado, pode evitar o surgimento de sequelas graves que vão impactar negativamente na vida do indivíduo (Kato et al, 2022) Apesar de inúmeras intervenções serem preconizadas, prevenir a DBP ainda é um desafio. Conforme exposto anteriomente, vários fatores estão envolvidos na patogênese da displasia broncopulmonar em recém-nascidos prematuros, incluindo as variações genéticas e o resultado delas que promove diferenças entre os indivíduos, podendo predispor ou não à DBP.…”
Section: Intervenções Para Prevenir Dbpunclassified
“…The following data were extracted: author information, title, journal, year of publication, identi ed risk factors, study design, and participants. The review protocol was published [21] and registered on the University Hospital Medical Information Network Clinical Trial Registry (registration number: UMIN000045529). This scoping review was reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Scoping Review Guideline [22].…”
Section: Data Chartingmentioning
confidence: 99%